Psychiatric Disorders in Elderly Patients attending OPD of Tertiary Care Centre in Eastern region of Nepal - Nepal, S.; Sapkota, N.; Kumar, R.; Deo, B.K.; Mishra, S. (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: Nearly 25% of the elderly peoples have significant psychiatric symptoms. Although mental disorders are common among elderly all over the world, information on the extent and types of geriatric psychiatric disorder is limited in our settings. Objective: To find out the prevalence of different psychiatric morbidities in elderly population and to study associated demographic variables. Method: A total of 210 consecutive elderly (60 years and older) patients in psychiatric OPD were enrolled in a period of one year, after taking informed consent. Mini Mental State Examination (MMSE) was done as screening tool for the assessment of cognitive impairment. Diagnoses were made according to ICD-10 guidelines. Data were analysed using SPSS. Result: Out of 210 cases, females slightly outnumbered males. The mean age of patients was 67.29 years ± 7.302. Most of the patients were Hindu by religion, illiterate and married. Most common primary psychiatric illness was Depression (n=77, 36.7%) followed by Neurotic, stress related and somatoform disorders (n= 29, 13.8%). Twenty seven patients (12.9%) had alcohol dependence syndrome, twenty four cases (11.4 %) had Dementia, seventeen cases (8.1%) had Bipolar affective disorder, thirteen cases were of schizophrenia and other psychotic illnesses. Conclusion: : Depression was the most common psychiatric illness among geriatric population followed by anxiety spectrum disorders, alcohol dependence syndrome and dementia.